2012
DOI: 10.1063/1.4757292
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing diode thickness for thin-film solid state thermal neutron detectors

Abstract: In this work, we investigate the optimal thickness of a semiconductor diode for thin-film solid state thermal neutron detectors. We evaluate several diode materials, Si, CdTe, GaAs, C (diamond), and ZnO, and two neutron converter materials, 10B and 6LiF. Investigating a coplanar diode/converter geometry, we determine the minimum semiconductor thickness needed to achieve maximum neutron detection efficiency. By keeping the semiconductor thickness to a minimum, gamma rejection is kept as high as possible. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 16 publications
1
26
0
Order By: Relevance
“…Murphy et al investigated the optimal thickness of a semiconductor diode for thin‐film solid‐state thermal neutron detectors. They investigated a coplanar diode/converter geometry to determine the minimum semiconductor thickness needed to achieve maximum neutron detection efficiency.…”
Section: Areas Of Nntmentioning
confidence: 99%
“…Murphy et al investigated the optimal thickness of a semiconductor diode for thin‐film solid‐state thermal neutron detectors. They investigated a coplanar diode/converter geometry to determine the minimum semiconductor thickness needed to achieve maximum neutron detection efficiency.…”
Section: Areas Of Nntmentioning
confidence: 99%
“…Murphy et al reported that Si provides better gamma-ray rejection compared with other semiconductor materials, i.e. C (diamond), ZnO, GaAs, and CdTe [14].…”
Section: Introductionmentioning
confidence: 97%
“…Two categories of solid-state devices have been demonstrated in literature: indirect conversion and direct conversion heterostructures. Indirect conversion device geometries place a thin film of neutronsensitive material within range of, but external to, an adjacent space-charge layer (LiCausi 2008, Caruso 2010, Melton 2011, Dahal 2012, Murphy 2012. In contrast, direct conversion heterostructures contain a neutron-sensitive material that can also be the space-charge layer (Robertson 2002;Caruso 2006Caruso , 2010Hong 2010).…”
Section: Review: Solid-state Neutron Detectorsmentioning
confidence: 99%